An Indigenous Public Sphere? The Media and the 2009 Sámediggi Election Campaign - Josefsen, Eva; Skogerbø, Eli (Arctic Review on Law and Politics, 2013)
This article discusses media coverage of the Norwegian Sámediggi election campaign in 2009, focusing on the research question: Did Sami voters, scattered over a vast geographical area and split into multiple language groups, have a public space in the media, where Sami politics could be discussed ahead of the Sámediggi elections in 2009? Our findings show there was indeed a public space for Sami politics, but unequal communication opportunities for Sami voters, depending on language and geography. In the north the media provided a bilingual public space, as both Sami and Norwegian newspapers covered the election. Voters in the south were offered less news and debate about the Sámediggi election and coverage was most likely to be in Norwegian. One explanation for these differences is that the number of Sami voters is small, and further south the voters are fewer and more scattered. The differences were also explained in terms of relevance of issues. The degree of conflict and controversy over Sami politics is higher in Finnmark than in other parts of Sápmi and Norway.Keywords: Media, Sami, Parliament, Sámediggi, election, NorwayCitation: Arctic Review on Law and Politics, vol. 4, 1/2013 pp. 62–89. ISSN 1891-6252